Effects of environmental conditions on healthcare worker wellbeing and quality of care: A qualitative study in Niger. - Darcy M Anderson; Ezechiel Mahamane; Valerie Bauza; Kairou Oudou Bilo Mahamadou; Lucy Tantum; Aaron Salzberg (Public Library of Science (PLoS), 2023)
Environmental conditions (water, sanitation, hygiene, waste management, cleaning, energy, building design) are important for a safe and functional healthcare environment. Yet their full range of impacts are not well understood. In this study, we assessed the impact of environmental conditions on healthcare workers' wellbeing and quality of care, using qualitative interviews with 81 healthcare workers at 26 small healthcare facilities in rural Niger. We asked participants to report successes and challenges with environmental conditions and their impacts on wellbeing (physical, social, mental, and economic) and quality of care. We found that all environmental conditions contributed to healthcare workers' wellbeing and quality of care. The norm in facilities of our sample was poor environmental conditions, and thus participants primarily reported detrimental effects. We identified previously documented effects on physical health and safety from pathogen exposure, but also several novel effects on healthcare workers' mental and economic wellbeing and on efficiency, timeliness, and patient centeredness of care. Key wellbeing impacts included pathogen exposure for healthcare workers, stress from unsafe and chaotic working environments, staff dissatisfaction and retention challenges, out-of-pocket spending to avoid stockouts, and uncompensated labor. Key quality of care impacts included pathogen exposure for patients, healthcare worker time dedicated to non-medical tasks like water fetching (i.e., reduced efficiency), breakdowns and spoilage of equipment and supplies, and patient satisfaction with cleanliness and privacy. Inefficiency due to time lost and damaged supplies and equipment likely have substantial economic value and warrant greater consideration in research and policy making. Impacts on staff retention and care efficiency also have implications for health systems. We recommend that future research and decision making for policy and practice incorporate more holistic impact measures beyond just healthcare acquired infections and reconsider the substantial contribution that environmental conditions make to the safety of healthcare facilities and strength of health systems.